Utilization of Cloud Computing Technology in E-Learning SMK PGRI 4 Pasuruan - Riono, Sapto Hadi; Hadiatullah, Dimas Rega; Rahma, Fatikh Inayahtur (International journal of technology and education research, 2024)
Learning activities at the SMK PGRI 4 Pasuruan school still use the conventional model, namely face-to-face, so it is necessary to develop online learning media or what is now often referred to as e-learning to help teachers and students take material and do assignments online. With online learning, it is hoped that teachers can update learning materials and students can access them without being constrained by place and time, besides that assignments to students can be well controlled. In general, all SMK PGRI 4 Pasuruan schools have the same business processes as well as system and information technology requirements. However, in reality, each school develops its architecture and information system separately. On the other hand, the majority of schools do not have sufficient budget to procure infrastructure to support the information systems needed, especially for learning activities such as e-learning. This research uses the Agile Software Development method. This research aims to help the SMK PGRI 4 Pasuruan school improve the quality of learning by utilizing e-learning learning media without having to think about the procurement, installation and configuration of hardware or software.